2016
DOI: 10.1186/s40176-016-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Income, amenities and negative attitudes

Abstract: We exploit the regional variation in negative attitudes towards immigrants to Sweden in order to analyse the consequences of negative attitudes on refugees' utility from labour income and amenities. We find that attitudes towards immigrants are important: while they affect mainly the refugees' quality of life, they also affect their income. We estimate the utility effects of negative attitudes for refugees with different levels of education and gender. We also analyse how the size of the refugees' networks rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
5
0
3
Order By: Relevance
“…Income is a necessity for payment. Some studies showed that income is an important factor on the attitude of individuals [44,45] and has a direct effect on WTP [9]. There is a statistically significant relationship between livestock and attitude to pricing at a level of p < 0.01.…”
Section: Discussionmentioning
confidence: 96%
“…Income is a necessity for payment. Some studies showed that income is an important factor on the attitude of individuals [44,45] and has a direct effect on WTP [9]. There is a statistically significant relationship between livestock and attitude to pricing at a level of p < 0.01.…”
Section: Discussionmentioning
confidence: 96%
“…These interesting findings are primarily descriptive in nature and likely linked to tangible living conditions, i.e., the fear of physical violence. Waisman and Larsen (2016) investigate the quasi-random variation in the initial placement of asylum seekers in Sweden in conjunction with measures of attitudes based on survey data, which they use to approximate migrants' living conditions and potential discrimination. They find some evidence that refugees' subsequent location choices are related to natives' surveyed attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время западные теоретики многосторонне исследуют различные аспекты влияния отношения принимающего сообщества на аккультурацию и натурализацию мигрантов. Г. Вайсман и Б. Ларсен на примере иммигрантов в Швеции показывают, что отношение к мигрантам со стороны местного населения влияет на доходы и в целом на качество жизни переселенцев [Waisman, Larsen 2016]. Опросы в США показали взаимосвязь восприятия местными жителями нелегальных иммигрантов с проблемой ощущения безопасности собственного существования .…”
Section: обзор литературыunclassified